Assessing efficacy and safety of buccally inoculated midazolam and intravenously administered diazepam for relieving pediatric primary generalized epileptic seizures - A. G. Prityko; K. V. Osipova; P. L. Sokolov; E. A. Ezhova; I. G. Kotel’nikova; E. G. Lukyanova; G. A. Osipova (Эпилепсия и пароксизмальные состояния)
Objective: to confirm a therapeutic equivalence and similar safety profile of “Midazolam, oromucosal (buccal) solution” and “Sibazon, solution for intravenous and intramuscular administration” used in children aged from 1 year to 18 years suffering from primary generalized and bilateral tonic, clonic and tonic-clonic seizures.Material and methods. An open-label, randomized clinical trial on efficacy and safety was conducted with 25 patients having primary generalized and bilateral tonic, clonic and tonic-clonic seizures due to epilepsy or epileptic syndrome. The study used age-appropriate doses of Midazolam with a single buccal administration as well as diazepam (Sibazon) for single intramuscular administration. Midazolam dosing was as follows: 5 mg for children of the younger age group (1 tube-dropper 5 mg/ml), 7.5 mg for children of the middle age group (1 tube-dropper 5 mg/ml and 1 tube-dropper 2.5 mg/ml), 10 mg for older children (2 tube-droppers 5 mg/ml). The drug effectiveness was assessed by primary and secondary criteria. The number of cases of drug administration in each group was used as the primary criteria, in which the convulsions ended up within 10 minutes after using the drug and did not resume within 60 minutes after drug administration. The following criteria were used as secondary: no repeated convulsive seizures within 24 hours after drug administration, no repeated convulsive seizure within 48 hours after drug administration, time before repeated convulsive seizure within 48 hours after drug administration. Clinical assessment was carried out according to clinical data, electroneurophysiologic (electroencephalographic) studies, electrocardiography, clinical blood and urine tests, aswell as biochemical blood tests by measuring glucose, total protein, albumin, total bilirubin, cholesterol, aspartate aminotransferase, alanine aminotransferase, creatine phosphokinase, alkaline phosphatase, creatinine, urea, and creatinine clearance level.Results. Compliance with the first efficacy criterion after using Midazolam and Sibazon was observed in 11 (84.6%) and 9 (75%) patients in Group 1 and Group 2, respectively, showing insignificant differences (Fisher's exact test (FET): p=0.645). The number of no cases of repeated convulsive seizure within 24 hours after drug administration differed significantly and was 12 (92.3%) and 6 (50%), respectively (FET: p=0.030). The number of cases with no second seizures within 48 hours after drug administration in Group 1 and Group 2 was 12 (92.3%) and 5 (41.7%), respectively, showing insignificant differences (FET: p=0.0112). No serious adverse events were reported during the study. No patients cancelled participation in the study due to developed adverse event.Conclusion. The data obtained evidence about compatibility of therapeutic efficacy profile and similar safety profile for “Midazolam, oromucosal (buccal) solution” and “Sibazon, solution for intravenous and intramuscular administration” that agrees with multiple data of earlier studies.